Characteristics of fine-scale turbulence noise evaluated by modal analysis. (March 2020) - Zhao, Wen; Jiang, Zaixiu; Wang, Xu; Mao, Dongxing
Highlights: Modal analysis is carried out to theoretically analyze the turbulence noise. This method is not subject to experimental constraints and frequency limitations. A rapid yet accurate method to predict fine-scale turbulence noise is proposed. Abstract: Jet flows are common in daily life such as from high-speed hair dryers, they are also used extensively in industrial settings for drying and cleaning applications. Turbulence noise from jet flows consists of large-scale and fine-scale structures. Modal analysis method with experimental data has already been applied to study the properties of large-scale turbulence noise. In this paper, spatial mode decomposition is used to theoretically analyze fine-scale turbulence noise based on a modified Tam–Auriault (TA) model. This makes our analysis of fine-scale turbulence noise not subject to experimental constraints. Using the proposed method, similarities and differences between the two scales of turbulence noise can be observed. It is found that the zero-order mode of fine-scale turbulence noise depends mainly on the turbulence scale, whereas the non-zero modes depend mainly on the non-compactness of the source. We also calculate the dominant mode at each frequency, which allows a rapid yet accurate prediction of fine-scale turbulence noise to be made. This work helps in understanding the generation and radiation of fine-scale turbulence noise.